Incidence and antimicrobial susceptibility profile of Staphylococcus aureus isolated from equipment of a sports academy in the city of Pouso Alegre, MG (Research, Society and Development, 2023)
The present study aimed to investigate the occurrence of Staphylococcus aureus in sports gym equipment and identify the antimicrobial susceptibility profile. The analysis was based on three samples from seven different pieces of equipment over three days, totaling 63 samples. Microorganism isolation was performed using the surface swab technique. Antimicrobial susceptibility testing followed the Clinical and Laboratory Standards Institute protocols, using drugs such as cefoxitin, clindamycin, chloramphenicol, erythromycin, gentamicin, sulfamethoxazole/trimethoprim, and tetracycline. All equipment contained Staphylococcus microorganisms, with S. aureus identified in five of them. Of the eight S. aureus isolates tested, five showed resistance to erythromycin, two to clindamycin, and two to cefoxitin, confirming its classification as MRSA. The presence of Staphylococcus sp. in equipment contrasts with the worrying resistance of some strains of S. aureus to erythromycin, clindamycin and cefoxitin, indicating MRSA. Resistance to these crucial antibiotics highlights the urgency of rigorous cleaning measures and new studies for specific guidelines to contain the spread in sports environments and protect the health of users.